2017
DOI: 10.1093/eurheartj/ehx037
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Standardized Neurological Endpoints for Cardiovascular Clinical Trials

Abstract: Surgical and catheter-based cardiovascular procedures and adjunctive pharmacology have an inherent risk of neurological complications. The current diversity of neurological endpoint definitions and ascertainment methods in clinical trials has led to uncertainties in the neurological risk attributable to cardiovascular procedures and inconsistent evaluation of therapies intended to prevent or mitigate neurological injury. Benefit-risk assessment of such procedures should be on the basis of an evaluation of well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 57 publications
0
42
0
2
Order By: Relevance
“…Furthermore, as the Neurologic Academic Research Consortium recommends, a systematic neurocognitive assessment of individuals undergoing TAVR is fundamental to better evaluating the safety and effectiveness of the procedure, including different delirium assessment tools. 53 Avoiding psychoactive drugs whenever possible; managing sleep, anxiety, and agitation; involving family members in care, particularly for reorientation and prevention of self-harm; encouraging mobility and self-care; assessing for and addressing pain; ensuring that patients have glasses, hearing aids, and dentures; normalizing electrolytes; and treating infections are other steps that can be taken. 12,14 To that end, a multidisciplinary collaboration with better participant selection will promote progressive, safe application of this promising technique.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the Neurologic Academic Research Consortium recommends, a systematic neurocognitive assessment of individuals undergoing TAVR is fundamental to better evaluating the safety and effectiveness of the procedure, including different delirium assessment tools. 53 Avoiding psychoactive drugs whenever possible; managing sleep, anxiety, and agitation; involving family members in care, particularly for reorientation and prevention of self-harm; encouraging mobility and self-care; assessing for and addressing pain; ensuring that patients have glasses, hearing aids, and dentures; normalizing electrolytes; and treating infections are other steps that can be taken. 12,14 To that end, a multidisciplinary collaboration with better participant selection will promote progressive, safe application of this promising technique.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low study size, thus lack of statistical significance, none of them demonstrated a statistically significant reduction in stroke at 30 days, yet they all reported fewer stroke numbers in the group with CEP. The challenges to establish an unambiguous efficacy in those studies are mostly because there has been an enormous variation in stroke definitions and some point of uncertainty about which end‐point is clinically relevant (See Proposed Standardized Neurological Endpoints in Cardiovascular Clinical Trials NeuroARC ) . Similarly, Guistino et al conducted meta‐analysis including the totality of RCTs (CLEAN‐TAVI, DEFLECT‐III, EMBOL X, MISTRAL C, SENTINEL), where the use of CEP appeared to be associated with notable (but nonsignificant) trend toward reduction in death or stroke (6.1% vs 9.6%; RR: 0.61; 95%CI: 0.35‐1.07; P = 0.08; I 2 = 0%) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapid evolution of this technology, lower‐profile devices, and increased operator experience, recent studies have raised concerns about adverse cerebrovascular event rates in patients undergoing TAVR . However, stroke frequency is highly dependent on the definition, varying in classification, ascertainment, and thresholds for detecting sub‐clinical events, thus often underdiagnosed and underreported in TAVR . Self‐reported stroke rates without prospective neurological evaluation likely underestimate true numbers and range from 9% up to 29% when neuroimaging is performed …”
Section: Introductionmentioning
confidence: 99%
“…It will be hard to demonstrate a clinical benefit of complete over incomplete filter protection, therefore future studies should focus on surrogate endpoints such as lesions on brain‐MRI or neurocognitive performance, as proposed by a recent academic research consortium consensus document .…”
Section: Discussionmentioning
confidence: 99%